A model of group mobility management based on user behavior prediction - Xiaoyong LIN; Yang YU; Zhengkun MI (Dianxin kexue)
Mobility management (MM) is a vital part of future 5G mobile communication.How to balance the paging loads and reduce the location update costs is a key topic in wireless communication research.A novel model of group mobility management based on user behavior prediction was proposed,in which users with the similar moving characteristics could be under unified management,thereby repeated costs from the traditional model of single mobility management (SMM) could be reduced.Simulation results show that GMM can get better running cost than SMM.